2007
DOI: 10.1534/genetics.106.066670
|View full text |Cite
|
Sign up to set email alerts
|

Cytotype Regulation by TelomericPElements inDrosophila melanogaster: Interactions WithPElements From M′ Strains

Abstract: P strains of Drosophila are distinguished from M strains by having P elements in their genomes and also by having the P cytotype, a maternally inherited condition that strongly represses P-element-induced hybrid dysgenesis. The P cytotype is associated with P elements inserted near the left telomere of the X chromosome. Repression by the telomeric P elements TP5 and TP6 is significantly enhanced when these elements are crossed into M9 strains, which, like P strains, carry P elements, but have little or no abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…However, in all cases, the level of repression was not significantly affected by the presence or absence of a telomeric P element in the F 2 females themselves. Simmons et al (2007a) made similar observations.…”
Section: Expression Of Telomeric P Elementssupporting
confidence: 60%
See 3 more Smart Citations
“…However, in all cases, the level of repression was not significantly affected by the presence or absence of a telomeric P element in the F 2 females themselves. Simmons et al (2007a) made similar observations.…”
Section: Expression Of Telomeric P Elementssupporting
confidence: 60%
“…The results (supplemental Table S4) indicate that in this hybrid context, TP6 was a weak repressor and TP5 was a negligible repressor. Thus, the moderate to strong repression seen in offspring of the TP-M5B#1 hybrids must be due to a synergism between the telomeric and M5B#1 P elements, as observed by Simmons et al (2007a). These results show that the native telomeric P elements, TP5 and TP6, interact synergistically with the M5B#1 P elements to repress GD, whereas the H(hsp/P) transgenes do not.…”
Section: Expression Of Telomeric P Elementsmentioning
confidence: 61%
See 2 more Smart Citations
“…Stuart et al (2002) added to this evidence by analyzing the regulatory abilities of two incomplete P elements, TP5 and TP6, inserted in the TAS at the left end of the X chromosome. Further study of these elements has shown that they regulate P activity in the germline but not in the soma, that their regulatory abilities are established and maintained in the female germline, that these abilities are passed on to offspring of either sex, and that, in at least some cases, they are transmitted to offspring independently of the telomeric P elements themselves Simmons et al 2004Simmons et al , 2007, accompanying article in this issue). However, neither TP5 nor TP6 appears to encode a polypeptide with any significant repressor function (Stuart et al 2002; P. Jensen, J. Stuart, M. Goodpaster, K. Newman, J. Goodman and M. Simmons, unpublished results).…”
Section: S Ince Its Discovery Bymentioning
confidence: 99%